“Global” Entanglements of a “Local” Medical Historian - Chen Hao (Revue d’Histoire des Sciences Humaines)
This paper proposes to explore the formation of a discipline named Chinese medical history in the early half of 20th century through a case study of a medical historian, Chen Bangxian, and his writings. Chen gained knowledge about recent trends in world medical history in his local world indirectly, when the thinking of historians in the German-speaking countries spread to other Western countries, to Japan, and finally to China. The article explores ways to understand the interaction between knowledge and historiography in the early half of 20th century in a global context, and reveals how a historiography which both embraced world trends and historians with limited transnational background at the same time created a new “modern” way to write medical history in Republican China.